Survival and Growth of Epiphytic Ferns Depend on Resource Sharing - Lu, Hua-Zheng; Song, Liang; Liu, Wen-Yao; Xu, Xing-Liang; Hu, Yue-Hua; Shi, Xian-Meng; Li, Su; Ma, Wen-Zhang; Chang, Yan-Fen; Fan, Ze-Xin; Lu, Shu-Gang; Wu, Yi; et al. (Frontiers in Plant Science, 2016)
Locally available resources can be shared within clonal plant systems through physiological integration, thus enhancing their survival and growth. Most epiphytes exhibit clonal growth habit, but few studies have tested effects of physiological integration (resource sharing) on survival and growth of epiphytes and whether such effects vary with species. We conducted two experiments, one on individuals (single ramets) and another on groups (several ramets within a plot), with severed and intact rhizome treatments (without and with physiological integration) on two dominant epiphytic ferns (Polypodiodes subamoena and Lepisorus scolopendrium) in a subtropical montane moist forest in Southwest China. Rhizome severing (preventing integration) significantly reduced ramet survival in the individual experiment and number of surviving ramets in the group experiment, and it also decreased biomass of both species in both experiments. However, the magnitude of such integration effects did not vary significantly between the two species. We conclude that resource sharing may be a general strategy for clonal epiphytes to adapt to forest canopies where resources are limited and heterogeneously distributed in space and time.